A culturomics approach to quantifying the salience of species on the global internet. Issue 4 (25th September 2019) - Ladle, Richard J.; Jepson, Paul; Correia, Ricardo A.; Malhado, Ana C. M.
Abstract: Conservation will only be successful over the long term if people support conservation goals. While many factors may influence the level of such support, it is clear that people are more willing to conserve species and places that they are familiar with and which provide them with something they value. Until now this dimension has been largely lacking from conservation decision‐making and its underlying scientific evidence base. This is understandable given conservation scientists' historic focus on population and community ecology and the practical difficulties associated with assessing the cultural prominence of species or places at anything more than local scale. This latter challenge is rapidly being addressed through a new generation of culturomic metrics that takes advantage of publicly available digital content. Here, we suggest that one such metric, estimated frequency of webpages that mention the scientific names of a species, broadly reflects the relative prominence of a species in global culture. Using all extant bird species as a case study, we demonstrate that species that are mentioned at high frequency on the global internet: (a) were scientifically described earlier, (b) have wide geographic ranges that overlap with technologically advanced societies, (c) are phenotypically conspicuous and (d) are strongly associated with direct human interactions (e.g. hunting). These results support the use of estimates of scientific name frequency on the internet as a proxy of a species' cultural salience, especially with respect to urban populations in technologically advanced societies. We conclude by discussing how a new generation of digital tools might be developed to support conservation monitoring and communication. A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. Abstract : A conservação a longo prazo só será bem‐sucedida se as pessoas apoiarem os objetivos de conservação. Embora muitos fatores possam influenciar o nível desse apoio, é evidente que as pessoas estão mais dispostas a conservar espécies e lugares familiares que lhes proporcionam algo que valorizam. Até agora, esta dimensão está faltando na prática da conservação e tem lacunas na base de informação científica. Isto é compreensível, dado o histórico do foco dos cientistas da conservação na ecologia das populações e das comunidades, e as dificuldades práticas de avaliar a proeminência cultural das espécies ou dos lugares em escalas espaciais grandes. Este último desafio está sendo rapidamente abordado através de uma nova geração de métricas baseadas em culturômica ( culturomics) que aproveitam a enorme quantidade de conteúdo digital disponível. Aqui, sugerimos que uma dessas métricas, a frequência estimada de páginas da Web que mencionam os nomes científicos de uma espécie, reflita a proeminência relativa de uma espécie na cultura global. Usando todas as espécies de aves existentes como um estudo de caso, demonstramos que as espécies mencionadas em alta frequência na Internet global: i) estão entre as primeiras a serem cientificamente descritas; II) tem ampla distribuição geográfica que se sobrepõem às sociedades tecnologicamente avançadas; III) são fenotipicamente distinto, e; IV) estão fortemente associadas com interações diretas com os seres humanos (por exemplo, caça). Nossos resultados apoiam o uso de estimativas de frequência de nomes científicos na Internet como uma métrica da saliência cultural de uma espécie, especialmente no que diz respeito às populações urbanas em sociedades tecnologicamente avançadas. Concluímos discutindo como uma nova geração de ferramentas digitais baseadas em culturomics pode ser desenvolvida para apoiar o monitoramento e a comunicação da conservação.